Laser shadow and interferometric investigation of the structure and dynamics of plasma in PF-3 facility - Krauz, V.I.; Karakin, M.A.; Myalton, V.V.; Vinogradov, V.P.; Krokhin, O.N.; Nikulin, V.Ya.; Oginov, A.V.; Gurey, A.E.; Tikhomirov, A.A. (Вопросы атомной науки и техники, 2005)
The work presents the laser investigation of a plasma focus discharge in neon. This investigation was done in connection with the recently discussed possibility of the use of such type of discharges for the creation of the soft X-ray source and its application for the compression of the solid targets (liners). Some features of a plasma focus discharge in 2.8 MJ Plasma Focus such as a complicated structure of current-plasma sheath (CPS), its relation to soft X-ray (SXR) pulse emitted from a pinching region were studied by developed laser diagnostics. У роботі представлене лазерне дослідження плазмово-фокусного розряду в неоні на установці ПФ-3. Дослідження були виконані в зв'язку з обговорюваною останнім часом можливістю використання такого типу розрядів для створення могутніх джерел м'якого рентгенівського випромінювання і їх застосування для стиску твердих мішеней (лайнерів). Деякі особливості плазмово-фокусного розряду в установці ПФ-3 такі, як складна структура струмо-плазмової оболонки і її зв'язок із властивостями імпульсу м'якого рентгенівського випромінювання, випромінюваного з області пінчування плазми, досліджені за допомогою розробленої лазерної діагностики. В работе представлено лазерное исследование плазмофокусного разряда в неоне на установке ПФ-3. Исследования были выполнены в связи с обсуждаемой в последнее время возможностью использования такого типа разрядов для создания мощных источников мягкого рентгеновского излучения и применения их для сжатия твердых мишеней (лайнеров). Некоторые особенности плазмофокусного разряда в установке ПФ-3 такие, как сложная структура токово-плазменной оболочки и ее связь со свойствами импульса мягкого рентгеновского излучения, излучаемого из области пинчевания плазмы, исследованы с помощью разработанной лазерной диагностики.